2013
DOI: 10.5424/sjar/2007053-5342
|View full text |Cite
|
Sign up to set email alerts
|

Short communication. PCR detection of DNA of bovine, ovine-caprine and porcine origin in feed as part of a bovine spongiform encephalopathy control program

Abstract: The rapid identification of residues of mammalian materials in animal feedstuffs is important for the effective control of feed as a potential source of transmission of bovine spongiform encephalopathy (BSE). It is included in the monitoring program developed to avoid the appearance of this disease. In the present work a PCR analysis was tested for the detection of mammalian residues (bovine, caprine, ovine and porcine). The DNA extraction method utilised guanidium thiocianate, and primers flanking a conserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…Anopheles stephensi and An. subpictus were also screened for bovine blood using specific primers by PCR as described by Corona et al [ 20 ]. The PCR conditions were: initial denaturation at 95 °C for 2 min; 10 cycles of denaturation at 94 °C for 1 min, annealing at 58 °C for 1 min, extension at 72 °C for 1 min 30 s; 20 cycles of denaturation at 90 °C for 1 min, annealing at 58 °C for 1 min, extension at 72 °C for 1 min 30 s; and final extension at 72 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Anopheles stephensi and An. subpictus were also screened for bovine blood using specific primers by PCR as described by Corona et al [ 20 ]. The PCR conditions were: initial denaturation at 95 °C for 2 min; 10 cycles of denaturation at 94 °C for 1 min, annealing at 58 °C for 1 min, extension at 72 °C for 1 min 30 s; 20 cycles of denaturation at 90 °C for 1 min, annealing at 58 °C for 1 min, extension at 72 °C for 1 min 30 s; and final extension at 72 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…It has been widely reported that identification of animal species by PCR analysis can be difficult in samples of complex composition, which have been subjected to intensive processing. Although DNA exhibits fairly high thermal stability, intense heat coupled with high pressure conditions may cause severe DNA degradation leading to difficulties in obtaining reliable results in PCR amplification, especially when the fragments to be amplified are too large (Arslan et al, 2006;Corona et al, 2007). Consequently, species identification in samples in which DNA is liable to be degraded must rely on amplification of short DNA targets (krcmar and Rencova, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…1 Currently, halal product demands increase globally not only for food and beverages but also encompass pharmaceutical products such as vaccines, medicines, and dental materials. 2 A positive response regarding halal problems, primarily regarding food, medicines, and cosmetics, has been projected by the Indonesian government by publishing several legislations, one of which is Law No. 33 of 2014 on Halal Product Guarantee (UUJPH).…”
Section: Introductionmentioning
confidence: 99%